2002
DOI: 10.1007/s00134-002-1314-6
|View full text |Cite
|
Sign up to set email alerts
|

Jejunal luminal microdialysate lactate in cardiac tamponade – effect of low systemic blood flow on gut mucosa

Abstract: Jejunal mucosal dysoxia and anaerobic metabolism occurs late during low systemic blood flow induced by experimental cardiac tamponade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
1
8
0
1
Order By: Relevance
“…Erst nach mehr als 60 min Ischämie kommt es zu einer beginnenden intrazellulären Laktatzunahme [29]. Die Abfolge dieser metabolischen Veränderungen ließen sich aus den erhobenen Daten komplett darstellen.…”
Section: Säure-basen-haushaltunclassified
“…Erst nach mehr als 60 min Ischämie kommt es zu einer beginnenden intrazellulären Laktatzunahme [29]. Die Abfolge dieser metabolischen Veränderungen ließen sich aus den erhobenen Daten komplett darstellen.…”
Section: Säure-basen-haushaltunclassified
“…It would be interesting and indeed supportive for the concept of "cytopathic hypoxia" [40] to confirm these data in a model with well preserved organ blood flow. This endotoxic shock model is characterized by a profound depression of systemic and regional blood flows which is paralleled by metabolic changes possibly related to tissue hypoperfusion [30,41,42]. Hence, it is clear that vasoactive treatments are associated with metabolic effects, which may reflect primarily their consequences on blood flow.…”
Section: The Adrenergic Coin: Perfusion and Metabolismmentioning
confidence: 99%
“…From human studies, it is difficult to establish which degree of CO reduction impairs GI metabolism, and in a clinical setting, this would be difficult or even impossible to investigate in a well-regulated manner. Previous animal studies using different methods of splanchnic blood flow reduction, however not limited to low cardiac output, have found that approximately a halving or more of GI blood flow induced a GI metabolic disorder, including decreased mucosal oxygen tension, mucosal pH and mesenteric oxygen uptake, and increased jejunal mucosal-to-arterial PCO 2 gradient [79]. Further metabolic consequences were increased mesenteric venous-arterial lactate difference and ß-hydroxybutyrate/acetoacetate ratio as well as increased intestinal intraluminal and intramural lactate concentrations and lactate/pyruvate ratios [7, 10].…”
Section: Introductionmentioning
confidence: 99%
“…Previous animal studies using different methods of splanchnic blood flow reduction, however not limited to low cardiac output, have found that approximately a halving or more of GI blood flow induced a GI metabolic disorder, including decreased mucosal oxygen tension, mucosal pH and mesenteric oxygen uptake, and increased jejunal mucosal-to-arterial PCO 2 gradient [79]. Further metabolic consequences were increased mesenteric venous-arterial lactate difference and ß-hydroxybutyrate/acetoacetate ratio as well as increased intestinal intraluminal and intramural lactate concentrations and lactate/pyruvate ratios [7, 10]. The specific methods for detection of splanchnic anaerobic metabolism, e.g., intestinal intraluminal and intramural microdialysis, jejunal tonometry, and jejunal mucosal oxygen tension, used in these studies are predominantly applicable in experimental investigations.…”
Section: Introductionmentioning
confidence: 99%